LKPD Stoikiometri Berbasis Inkuiri Terstruktur dengan Tiga Level Representasi untuk Kelas X SMA - Meni Lovia Melini; Minda Azhar (Universitas Negeri Padang, 2019)
This type of study is research and development (R and D) with 4-D development model. The research was conducted until the validity and practical test of the development. This student worksheet validated by 5 people validators namely 3 chemistry lectures and 2 chemistry teachers from SMAN 1 Linggo Sari Baganti. Practicality questionnaire was filled by 29 students of class XI and 2 chemical teachers of SMAN 1 Linggo Sari Baganti. The result showed that validity test is 0,87 categorized very high. The kappa moment of practical test by 2 chemstry teacher is 0,78 categorized high. The kappa’s moment of 29 students SMAN 1 Linggo Sari Baganti was 0,81 with a high practicality category.